Upaya Peningkatan Kemampuan Literasi Digital untuk Menanggulangi Hoaks bagi Siswa SMA Muhammadiyah 1 Pekanbaru - Sari, Yessi Ratna; Syam, Essy; Aris, Qori Islami (PUAN INDONESIA, 2024)
Nowadays, internet use can be accessed easily by various groups, especially among high school/vocational school students. Apart from the positive impacts obtained by users, the negative impacts of exposure to students via the internet are also very large. Students are often exposed to fake news on various social media platforms because of their unwise use. Therefore, the service team carries out community service activities. This activity aims to improve students' ability to read, receive and criticize all types of news so that they can prevent the spread of false information through digital literacy knowledge. Participants in the activity were 27 class X students at SMA Muhammadiyah 1 Pekanbaru. The approach method used is learning and understanding by providing material regarding digital literacy, exercises in the form of questions and answers including pre-test, post-test and discussions. The pre-test results show that around 80% of students are aware of the importance of digital literacy in everyday life. After providing material and discussion, a significant increase in students' understanding and awareness was obtained through the post-test, namely 96%. By carrying out this activity, it is hoped that students will be able to sort out positive information, ignore news that is provocative and spreads hatred.